Peer-led focus groups as 'dialogic spaces' for exploring young people's evolving values. Issue 5 (2nd September 2020) - Djohari, Natalie; Higham, Rupert
ABSTRACT: Although peer-led focus groups are widely used in research with children and young people, surprisingly little has been written that evaluates their methodological appropriateness. Drawing on data from 10 peer-led focus group sessions across 5 international schools, this article demonstrates how focus group discussions around moral and social values, which become more meaningful though the self-reflection provoked in encounters with different experiences and perspectives, can be advantageous for research. Peer-moderators, as both participants and facilitators, run focus groups that open dialogic spaces for exploratory talk that avoids the self-censure and deference that can emerge in the presence of an adult moderator. This is particularly important when participants are structurally disadvantaged and lack similar spaces for collaborative inquiry into their shared experiences. Video capture allows researchers in-depth access to these focus groups after the event, revealing evidentially and pedagogically rich dialogues.